Persistența motivațională și stilul de relaționare socială la studenți [Articol] - Scorohod, Nicoleta (CEP USM, 2020)
Motivational persistence implies a behavioral perseverance in achieving defined goals, the ability to remain permanently motivated for a longer period of time, to find interest and satisfaction in any task to be performed.The style of social relationship involves the connection between the student and his relationships with the world around him. Cooperation between people is important because, through communication, each person expresses their opinion, thoughts, emotions, exchange of experiences, etc.
Keywords: persistența motivațională; stilul de relaționare; studenți